PENGARUH DESENTRALISASI FISKAL PADA PERTUMBUHAN EKONOMI DENGAN KESERASIAN BELANJA DAERAH SEBAGAI VARIABEL PEMODERASI - Dwirandra, A.A.N.B. (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 8 No 2 (2013), 2013)
ABSTRACT This research aimed to get empirical evident of moderating impact of local expenditure properness to the influence of fiscal decentralization to economic growth in order to prove that the impact of fiscal desentralization was not linear but contingent to economic growth. Data had been tested and fulfill the classical assumption dan model fit test. Based on multiple regression, analyses concluded that local expenditure properness and fiscal decentralization influenced  economic growth, partially and simultaneously. Further, local expenditure properness increased the influence of fiscal decentralization toward economic growth with parameter of PDRB but not for parameters of PDRB per capita and IPM. Keywords: decentralization, economic growth,  index,  properness